PENANAMAN NILAI-NILAI MORAL AGAMA PADA ANAK USIA DINI (AUD) DENGAN MENGGUNAKAN MEDIA PERMAINAN DADU DI RAUDHATUL ATHFAL (RA) MUSLIMAT AL-WASHLIYAH DAMULI PEKAN - Yurlianis Yurlianis (STIT Al-Ittihadiyah Labuhanbatu Utara, 2025)
This study aims to explore and analyze the process of instilling religious moral values in early childhood (AUD) through the use of dice game media as a learning aid at RA Muslimat Al-Washliyah Damuli Pekan. The background of this research is based on the importance of shaping children's character and morality from an early age, which is a primary foundation in forming personality and noble character in the future. The research method used is descriptive qualitative, with data collection techniques including participatory observation, in-depth interviews with teachers and the head of RA, as well as documentation of learning activities. The dice game media are creatively modified by including religious symbols, commands for goodness, and educational images that are relevant to Islamic values. Research results show that the use of dice games in learning is very effective in attracting children's interest, increasing active participation, and accelerating their understanding of religious moral concepts such as honesty, trustworthiness, helping each other, and politeness. Teachers also find it easier to deliver material interactively, enjoyably, and without monotony. Children appear more enthusiastic and exhibit positive behavioral changes, both at school and at home.